The Histopathological study of lesions of nasal cavity, paranasal sinuses and nasopharynx in Eastern UP(India) - Alpana Bundela (Tropical Journal of Pathology and Microbiology, 2023)
ABSTRACT- BACKGROUNDMasses in the nasal cavity, paranasal sinuses and nasopharynx a hetergenous group of lesions with a broad spectrum of histopathology features,So careful histological workup is essential for a correct diagnosis and to determine extent of involvement and prompt treatment.The  present study has been conducted on 158 cases in the department of pathology, BRD Medical college , Gorakhpur.AIMS AND OBJECTIVE(1)To establish histopathological diagnosis of Inflammatory, benign and malignant lesions of nasal cavity, paranasal sinuses and nasopharynx(2) To categorize these lesions into non- neoplstic and neoplastic lesions and to study their histopathological patterns.(3) To compare findings of our study with other studies.MATERIAL AND METHOD         This was a prospective study of sinonasal lesions those were biopsied or surgically excised and received in pathology department. RESULTA total of 158 cases of nasal , paranasal lesions were reported during the study period.Out of total 158 cases, 135 cases were inflammatory and non-neoplastic  lesions,20 cases were benign and 03 cases were malignant lesions.Age ranged from 08 yrs to 78 yrs with male predominance and majority cases belonged to Hindu community.Out of 135 inflammatory or non neoplastic cases most common lesion was nasal polyp and among 20 benign cases, Inverted papilloma was the commonest lesion.Out of 03 malignant lesion, Squamous cell carcinoma was the predominant histological type of lesion.CONCLUSION- Nasal, Paranasal and Nasopharyngeal lesions comprises of wide spectrum of lesions but their clinical manifestations are very limited.Hence a careful histopathological examination is mandatory for proper diagnosis so that a correct and timely intervention can be made.In this study we concluded that in Eastern UP, malignant lesions of nasal , paranasal and nasopharyngeal regions are very less in comparison to inflammatory and benign cases.